ASSESSING THE ROLE OF STATE AND NON-STATE ACTORS IN PROMOTING ENVIRONMENTAL SECURITY: CASE STUDY OF ISYO HILLS ECOTOURISM DESTINATION IN RHEPANG MUAIF VILLAGE, JAYAPURA REGENCY - Lantang, Floranesia; Patading, Gusti; Yamin, Muhammad (Universitas Padjadjaran, 2024)
Deforestation has become the primary concern of environmental security in Jayapura Regency Papua Province due to massive logging and illegal wildlife hunting. This research focuses on the role of state and non-state actors in promoting environmental security in Rhepang Muaif Village Jayapura Regency through the Isyo Hills ecotourism destination. Indigenous peoples in Rhepang Muaif Village harbored concern about land clearing in their customary forest caused by palm oil company activities. To support the research, a qualitative research method with thematic analysis is conducted with primary and secondary data collection. This research found four main actors, namely the state/government, academics, NGOs, and the youth community. Each actor significantly contributes to supporting the achievement of environmental security in Rhepang Muaif village. The government plays a role in forming regulations that support conservation and infrastructure assistance. Academics play a role in conducting research and community services. Additionally, NGOs play a role in the initial mapping of Rhepang Muaif village and its biodiversity potential. Meanwhile, the youth community plays an important role in promoting ecotourism and raising the potential of this village to receive the 2024 Tourist Village Award.